2020
DOI: 10.1051/e3sconf/202021104010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of students to distance learning in COVID-19 conditions in terms of ultradian rhythms of the cardiovascular system

Abstract: The emergence of the COVID-19 pandemic has led to the transition of educational organizations to self-isolation and distance learning. Once in the new conditions, it was necessary to adapt to the fact that the training format had changed. One of the important tasks for us was to study students’ health and the peculiarities of their adaptation to the acquisition of knowledge and skills using information and communication technologies remotely. Based on Ryazan State University, studies carried out aimed at study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Researchers reported that the cardiorespiratory system is most sensitive to environmental influences [8]. When solving cognitive problems, attentional tension is associated with a high level of HRV indicators [12][13][14][15]. It is observed that people with high HRV are more stressresistant and resistant to environmental changes 16.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that the cardiorespiratory system is most sensitive to environmental influences [8]. When solving cognitive problems, attentional tension is associated with a high level of HRV indicators [12][13][14][15]. It is observed that people with high HRV are more stressresistant and resistant to environmental changes 16.…”
Section: Introductionmentioning
confidence: 99%